Preseason weight-bearing ankle dorsiflexion in male professional football players with and without a history of severe ankle injury: A novel analysis in an English Premier League club - Clark, N. C.; Campbell, S. D. (Physical Therapy in Sport, 2021)
Objectives Ankle injuries are common in professional football and have profound player/team/club consequences. The weight-bearing lunge-test (WBLT) assesses ankle dorsiflexion range-of-motion in football primary/secondary injury prevention and performance contexts. Data for uninjured and previously ankle-injured players in the English Premier League (EPL) is not available. This study analysed WBLT measurements (cm) within and between uninjured and previously severe ankle-injured players (injured-stiff group, injured-lax group) in one EPL club.